GAMBARAN RESPONSE TIME DAN LAMA TRIAGE DI INSTALASI GAWAT DARURAT (IGD) DI RSUD KARAWANG - Sherly, Sherly; Rina Fera; Andriyansyah, Andriyansyah (Jurnal Cakrawala Ilmiah, 2022)
Emergency is a conditional that requires immediate handling to eliminate the threat of the patient life. All action taken in the emergency room must be truly effective and afficient, because patients will lose their lives in just minute. Response time is the time of intervention in emergency area that started from the patient coming until gets initial assesment. Triage is the process of selecting and sorting patients based on their priority level of emergency. The purpose of this study was to determine the description of response time and triage duration at emergency department RSUD Karawang. Reseach methods with cross sectional approach. Selection of samples with total sampling by 21 respondents. Instrument research using observation sheets. The result showed that the average response time and triage duration for 30 days was 55,66 seconds (0,92 minutes) and 41,66 seconds (0,69 minutes). More rapid response time and triage duration will affect to the patient, the faster handling to the patient will be treated the risk of getting worse the patient’s condition will decrease. Response time and triage duration in emergency department RSUD Karawang was according to standarts.